Peran Jaksa Dalam Melakukan Penuntutan Terhadap Perkara Tindak Pidana Korupsi Perspektif Hukum Islam - Abdain Abdain; Atnur Suljayestin (Datuk Sulaiman Law Review (DaLRev), 2020)
ABSTRACTThe role of the prosecutor's office in prosecuting cases of criminal acts of corruption starts when the case has not been transferred to the Court until the implementation of the court's decision, including receiving notifications, examining case files, conducting pre-prosecution, detaining, making indictments, closing cases, and transferring cases to court, bringing cases to justice the accused went to trial, read out the indictment, presented witnesses, prepared evidence, read out the indictment, and carried out the court's decision. In prosecuting corruption, the witnesses was not cooperative in providing information regarding the alleged corruption crime or as a witness to the alleged corruption crime, because they are afraid of superiors, the existence of suspects and witnesses who often move places so that it hinders the examination process. conduct identification of evidence, especially in relation to assets owned by the suspectÂ ABSTRAKPeranan kejaksaan dalam hal penuntutan perkara tindak pidana korupsi dimulai saat perkara belum dilimpahkan ke Pengadilan sampai pada pelaksanaan putusan pengadilan, mencakup menerima pemberitahuan, memeriksa berkas perkara, melakukan prapenuntutan, melakukan penahanan, membuat surat dakwaan, menutup perkara, dan melimpahkan perkara ke pengadilan, menghadapkan terdakwa ke persidangan, membacakan surat dakwaan, menghadapkan saksi-saksi, menyiapkan barang bukti, membacakan surat tuntutan, dan melaksanakan putusan pengadilan.Â  Dalam melakukan penuntutan tindak pidana korupsi adalah tidak koperatifnya para saksi dalam memberikan keterangan terkait adanya dugaan tindak pidana korupsi maupun sebagai saksi pada dugaan tindak pidana korupsi, karena takut kepada atasan, keberadaan tersangka dan saksi yang sering berpindah-pindah tempat sehingga menghambat proses pemeriksaan, susahnya melakukan identifikasi terhadap barang bukti terutama terkait dengan harta kekayaan yang dimiliki tersangka.